ID: 79. Issue 1 (November 2015) - Bongartz, Hannes; Hessenkemper, Wiebke; Wolf, Alexandra; Eulenfeld, René; Simister, Philip C.; Behrmann, Iris; Tavernier, Jan; Feller, Stephan M.; Haan, Claude; Schaper, Fred
<x xml:space="preserve">Abstract</x> The activating JAK2-V617F mutation is found in many patients suffering from Myeloproliferative neoplasms such as Polycythemia Vera and Essential Thrombocythemia. JAK2-V617F mutation confers cytokine hypersensitivity, constitutive activation of the JAK-STAT pathway, and cytokine-independent growth. We demonstrate uncontrolled membrane binding of the multi-site docking protein Gab1 in JAK2-V617F expressing cells. We elaborated the molecular mechanism and regulation of Gab1-membrane recruitment. In line with the regulatory function of Gab1 on STAT-independent signalling we show that PI3K signalling regulates MAPK activation in JAK2-V617F-positive cells. This cross-regulation of the MAPK pathway by PI3K affects JAK2-V617F-specific target gene induction, erythroid colony formation, and regulates proliferation of JAK2-V617F-positive patient cells in a synergistically manner. In summary, our study demands to consider cross-talk mechanisms as potential new targets. This may increase the specificity for intervention approaches compared to the interference in very upstream signalling elements such as receptor kinases or receptor-associated kinases.